2023
DOI: 10.3390/ijms241311100
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Prostate Cancer, the ‘Tousled Way’

Abstract: Androgen deprivation therapy (ADT) has been the mainstay of prostate cancer (PCa) treatment, with success in developing more effective inhibitors of androgen synthesis and antiandrogens in clinical practice. However, hormone deprivation and AR ablation have caused an increase in ADT-insensitive PCas associated with a poor prognosis. Resistance to ADT arises through various mechanisms, and most castration-resistant PCas still rely on the androgen axis, while others become truly androgen receptor (AR)-independen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 150 publications
0
4
0
Order By: Relevance
“…There are ongoing efforts to develop TLK1 and TLK2 inhibitors for targeting cancer cells with their promising roles in maintaining genome stability (64)(65)(66). Emerging evidence demonstrated that TLK1 and TLK2 are involved in cancer progression and therapeutic resistance (67)(68)(69)(70) and it has been shown that inhibition of TLK potentiates cell-killing in different types of cancers (1,(70)(71)(72)(73)(74), making TLK 1 and 2 attractive targets for therapeutic strategy development.…”
Section: Discussionmentioning
confidence: 99%
“…There are ongoing efforts to develop TLK1 and TLK2 inhibitors for targeting cancer cells with their promising roles in maintaining genome stability (64)(65)(66). Emerging evidence demonstrated that TLK1 and TLK2 are involved in cancer progression and therapeutic resistance (67)(68)(69)(70) and it has been shown that inhibition of TLK potentiates cell-killing in different types of cancers (1,(70)(71)(72)(73)(74), making TLK 1 and 2 attractive targets for therapeutic strategy development.…”
Section: Discussionmentioning
confidence: 99%
“…These include, for example: topoisomerase poisons, bleomycin, MMC, PARPis, and cisplatin, all of which ultimately lead to the formation of SSBs and DSBs. For some of these (e.g., doxorubicin and cisplatin), direct evidence of synthetic lethality in combination with TLK inhibitors has already been verified [38,61]. Of particular note is the reported synthetic lethal interaction of combining the knock down of TLKs with PARP inhibitors [36], which could be expected to engender a double hit on both NHEJ and HRR based on the already described functions of TLKs.…”
Section: Conclusion: Targeting Tlk1 For Cancer Treatmentmentioning
confidence: 95%
“…15 Recent studies have revealed a probable link between PCa, AD, and ADT, enticing further research into the underlying mechanisms and clinical implications. 17 ADT, a conventional treatment strategy in advanced PCa, seeks to decrease androgen signalling, hence preventing tumour development and progression. However, research studies suggest that extended ADT might have unforeseen consequences for cognitive function, possibly exposing people to neurodegenerative illnesses like AD.…”
Section: Dovepressmentioning
confidence: 99%
“… 15 Recent studies have revealed a probable link between PCa, AD, and ADT, enticing further research into the underlying mechanisms and clinical implications. 17 …”
Section: Introductionmentioning
confidence: 99%